Health Education Audiovisual Berbasis Health Belief Model (HBM) terhadap Perilaku Kepatuhan Pasien Tuberkulosis - I Kadek Karisma Wijaya; Linlin Handayani; Nandang Ahmad W; Blacius Dedi; Asep Badrujamaludin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of audiovisual health education based on the Health Belief Model (HBM) on the compliance behavior of tuberculosis patients in Kendari City. The method used a quantitative research type using a quasy-experiment design, namely the pre-post control group design. Research results show that Analysis of paired t tests, showed significant results on the variables of adherence to medication, fulfillment of nutrition and prevention of transmission (p < α = 0.05). The MANOVA test showed that the most influential variable in the intervention group was prevention of transmission (p<0.005) compared to medication adherence and nutrition fulfillment. The conclusion is audiovisual health education based on the Health Belief Model (HBM) can improve TB patient compliance behavior in taking medication, fulfilling nutrition and preventing transmission of tuberculosis patients in Kendari City. Keywords: Education, Fulfillment of Nutrition, Health Belief Model, Taking Medication